Fabrication of electrochemical sensor based on multi-walled carbon nanotubes/gold nanoparticles for voltammetric detection of amoxicillin and thiamphenicol residues in bovine milk - Muhammad, Aliyu (2016)
Antibiotic residues in milk are of great concern to health regulatory agencies, milk consumers and dairy farmers due largely to their effects ranging from allergic reactions, antibiotic resistance and ability to interfere with the technological properties of milk used for manufacturing fermented products. The conventional methods used in detecting these residues suffered some limitations of being expensive, time consuming and lack the capacity for point of care analysis. A bulk scale synthesis of nanocomposites containing gold nanoparticles (AuNPs) and multi-walled carbon nanotubes (MWCNTs) using ethylenediamine (en) as a cross linker between MWCNTs and AuNPs is presented here. The amine groups in en were used as growth point for the AuNPs synthesis through electrostatic attraction between the amine group (NH4+) and AuCl4- while sodium citrate acts as a reducing agent. The results showed that the size and distribution of AuNPs on the surface of the MWCNTs is greatly affected by the amount of HAuCl4. Morphology of the synthesized nanocomposites was characterized by Field Emission Scanning Electron Microscopy and Transmission Electron Microscopy while the elemental composition and crystallography of the composites were investigated by Energy Dispersive X-ray, Xray Diffraction, Ultraviolet Visible, Thermal Gravimetric Analysis and Raman spectroscopic techniques. The nanocomposite was used to modify a screen printed electrode. Electrochemical characterization of the electrode revealed that the nanocomposites have increased its electro-active surface area and conductivity. The fabricated sensor was applied for the voltammetric detection of amoxicillin in Bovine milk samples by adsorptive stripping voltammetry (AdSV). The result shows that the synthesized nanocomposites had induced a remarkable synergetic effect towards electro-oxidation of amoxicillin. Under optimized experimental conditions, (0.1 M phosphate buffer of pH 7.0, accumulation potential -0.4 V, accumulation time 180 s.) AdsV measurements of amoxicillin showed a wide linear dynamic range within the concentration range of 0.2-30 μM. Two linear calibration ranges from 0.2-10 μM and 10-30 μM were observed with equations of Ipa (μA) = 2.88 C (μM) + 1.2017; r = 0.9939 and Ipa (μA) = 0.88 C (μM) + 22.97; r = 0.9973 respectively. The limit of detection (LOD) and limit of quantification (LOQ) were calculated as 0.015 μM and 0.149 μM, respectively. Differential pulse voltammetric technique (DPV) was employed for thiamphenicol detection. The result shows that the synthesized nanocomposites also induced a remarkable synergetic effect for the oxidation of thiamphenicol. Under optimized experimental conditions, (0.1 M citrate buffer of pH 6.0, accumulation potential -0.7 V, accumulation time 150 s). DPV measurements of thiamphenicol shows a wide linear dynamic range within the concentration range of 0.1-30 μM. Two linear ranges were recorded from 0.1- 10 μM and 10-30 μM with equations of Ipa (μA) = 0.9888 C (μM) + 1.2563; r = 0.9939 and Ipa (μA) = 0.216 C (μM) + 7.36; r= 0.9973 with LOD and LOQ of 0.003 μM and 0.01.0 μM respectively. The fabricated sensor was applied for determination of amoxicillin and thiamphenicol in Bovine milk with satisfactory recovery results which compared favorably with HPLC standard method. This suggests its applicability as an alternative means of detecting amoxicillin and thiamphenicol in Bovine milk samples for environmental monitoring and quality control processes.